O postulado da participação popular em planos urbanísticos: uma análise comparada entre o Plano Diretor Participativo de Fortaleza (2009) e o Plano Fortaleza 2040 (2016) - Pinheiro, Samuel Tavares (2019)
In the evolutionary context of the Brazilian urban policy, the popular engagement had been absent in planning and management processes until the promulgation of the Federal Constitution of 1988. Since then and as opposed to the previous rational-technocratic model of planning, the urbanistic practice began to give special attention to collaborative approaches strongly inspired by deliberative democracy ideas and by debates that follow their spreading. Meanwhile, the flourishing of methods and tools of participation developed a fertile soil for instrumental diversification and contrasting results. This is particularly visible when comparing its application in previous urbanistic plans from the two techno-ideological matrices which became a reference among us: the reformist and the neoliberal. The first is based on distributivist ideals which have the objective of promoting special justice and the right to a city in a social development perspective. The second comprises the urban under an entrepreneur optic, offering support for attracting capital and adopting flexible actions in order to increase economic development. This scenario of differentiation and competition is the starting point of this research, which has as main goal reflecting on the social reach and political and institutional arrangements for popular engagement in the elaboration of urbanistic plans. The undertaken investigation takes in consideration the study of the two last documents conceived for the city of Fortaleza: Plano Diretor Participativo (2009) and Plano Fortaleza 2040 (2016). The methodological procedures listed to elucidate the nature of participatory processes are anchored in a compared analysis systematized in four dimensions: (I) social-political conjuncture of the city; (II) organizational structure and actors involved; (III) engagement methods and tools; (IV) temporal range and territorial coverage. The research results indicate that urbanistic plans with distinct technic-ideological goal are differentiated when it comes to official discourse and procedural rite, although concurring on a same expectation of information flow control and data consolidation. It must be noted that none of the two analyzed participatory arrangements reveals itself as social integration vector, due to the fact that they are not consisted as civil solidarities driving force that produces the democratic ways of life in the city.